PERKEMBANGAN BAHASA ANAK USIA DINI: ANALISIS TREN PENELITIAN MELALUI SYSTEMATIC LITERATURE REVIEW (2020-2025) - Dilla, Mutia Rachma; Asep Kurnia Jayadinata (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Early childhood language development is a fundamental aspect of a child's growth and development forms the basis for cognitive, social, and academic abilities in later life. This study aims to analyze research trends on early childhood language development in the period 2020–2025 using the Systematic Literature Review method. A total of 50 national and international journal articles that met the inclusion criteria were analyzed using a thematic analysis approach. The results of the study show that the dominant research themes include the role of the family environment, play-based learning in Early Childhood Education institutions, the use of digital media, and early detection and intervention of language development disorders. These findings confirm that the quality of verbal interaction between children and adults, contextual and enjoyable learning approaches, and the controlled and supervised use of digital media play a significant role in children's language development. The implications of this study emphasize the importance of collaboration between parents and educators in providing optimal language stimulation and the need for early intervention strategies for children with language delays. Theoretically and practically, this study contributes to the development of early childhood education studies.